FACTORS ASSOCIATED WITH ENTREPRENEURIAL INNOVATION IN INDEPENDENT PRACTICE SERVICES MIDWIVES IN SOUTHEAST ACEH DISTRICT IN 2024 - Surbakti, Imran Saputra; Ernawati; Sari, Devi Yulika; Zuliani, Cut; Batubara, Zulkarnain; Bakara, Sri Muliana Putri; Barus, Andhika Pratama (Yayasan Nuraini Ibrahim Mandiri, 2024)
This study aims to analyse the factors associated with entrepreneurial innovation in the service of Independent Midwife Practice (PMB) in Southeast Aceh District in 2024. Innovation in midwifery practice is crucial in improving service quality and competitiveness, especially in the context of public health services. This study used an observational method with a cross-sectional design. Data were collected through questionnaires distributed to 53 midwife leaders in Southeast Aceh District. The results showed that the training history variable had a significant relationship with entrepreneurial innovation (p-value = 0.008), while education, age, length of service, and knowledge factors did not show a significant relationship. The majority of respondents had a high level of education (100%), were over 35 years old (98%), had more than one year of work experience (100%), and had attended more than one training related to innovation and entrepreneurship (100%). However, only 42% of the respondents demonstrated innovation in their services. The conclusion of this study is that training history is the most influential factor on entrepreneurial innovation in PMBs in Southeast Aceh District. It is recommended that more intensive and sustainable training be held to increase the capacity of midwives' innovation in midwifery services.